Specificities of the intestinal microbiota in patients with inflammatory bowel disease and Clostridium difficile infection. (2nd January 2018) - Sokol, Harry; Jegou, Sarah; McQuitty, Claire; Straub, Marjolene; Leducq, Valentin; Landman, Cecilia; Kirchgesner, Julien; Le Gall, Guillaume; Bourrier, Anne; Nion-Larmurier, Isabelle; Cosnes, Jacques; Seksik, Philippe; et al.
ABSTRACT: Clostridium difficile infection (CDI) is a common complication in inflammatory bowel disease (IBD) and has been associated with poor IBD outcome. Intestinal microbiota composition in IBD patients with CDI has not been specifically evaluated to date. The fecal microbiota of 56 IBD patients, including 8 in flare with concomitant CDI, 24 in flare without CDI, and 24 in remission, as well as 24 healthy subjects, was studied using 16S sequencing. Analysis was performed using the Qiime pipeline. Compared to IBD patients without CDI, IBD patients with CDI had more pronounced dysbiosis with higher levels of Ruminococcus gnavus and Enterococcus operational taxonomic units (OTUs) and lower levels of Blautia and Dorea OTUs. Correlation network analysis suggested a disrupted ecosystem in IBD patients in flare, particularly in those with CDI. In patients with IBD, CDI is associated with a more pronounced intestinal dysbiosis with specific alterations in intestinal microorganisms.